Efficacy of the herbal preparation STW 5 in multi-target therapy of functional dyspepsia - A. A. Sheptulin; V. O. Kaybysheva (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To discuss mechanisms of action and results of clinical application of plant-derived drug STW 5 (Iberogast®) for treatment of functional dyspepsia (FD).Key points. Iberogast® is the combined agent containing extracts of 9 medicinal plants. Mechanism of action includes effect on motility of the stomach and intestine, visceral sensitivity along with anti-inflammatory and cytoprotective effects. Controlled clinical trials have confirmed high efficacy of Iberogast® at treatment of FD (including pediatric practice) as well as good tolerability of the drug.Conclusion. Results of Iberogast® application allow to consider its as effective agent in multi-target therapy of FD.